Comparative Study of Laterite and Bentonite Based Organoclays: Implications of Hydrophobic Compounds Remediation from Aqueous Solutions - Muhammad Nafees (The Scientific World Journal, 2013)
Four cost effective organoclays were synthesized, characterized, and studied for the sorption of hydrophobic compounds (edible oil/grease and hydrocarbon oil) from aqueous solutions. Organoclays were prepared by cation exchange reaction of lattice ions (present onto the surface of laterite and bentonite clay minerals) with two surfactants, hexadecyl trimethyl ammonium chloride (HDTMA-Cl) and tetradecyl trimethyl ammonium bromide (TDTMA-Br). Fourier transform infrared spectroscopy and scanning electron microscopy were used for the characterization of synthesized organoclays. It was found that the amount of surfactant loading and the nature of the surfactant molecules used in the syntheses of organoclay strongly affect the sorption capacity of the clay mineral. Further, it was found that both the laterite and bentonite based organoclays efficiently removed the edible and hydrocarbon oil content from lab prepared emulsions; however, the adsorption capacity of clay mineral was greatly influenced by the nature of hydrophobic compounds as well.